Determinants of dropping out of school: the case of Vietnam - Le, Thi Nhat Phuong (Kansas State University, 2008)
This paper describes the socioeconomic determinants of school dropout for Vietnamese children aged 11-18. It seeks to answer the following two questions: 1) What is the magnitude of the dropout rate for children between the ages of 11-18 and how does this figure change over time? 2) What are the determinants that affect the decision to drop out of school? This paper is based largely on the two Vietnam Living Standard Surveys (VLSS) conducted in 2004 and 2006. A probit model is used to ascertain the major determinants affecting the probability to drop out of school. The decision to drop out of school is affected by key factors including the child’s demographic characteristics (such as age, gender, ethnicity, and regions where they are living) and the child’s household’s situation (such as income per capita, cost of schooling, household size, and parental education). In particular, age and household size have significantly positive effects on the dropout probability. The dropout rate is also shown to vary between girls and boys, but this gender gap has narrowed substantially. Minority girls face more obstacles in staying school than minority boys. The school dropout rate is also very sensitive to changes in the household’s income and cost of schooling. However, the cost of schooling has different impacts on families in different quintiles. Region is another determinant affecting child’s decision to drop out of school. Vietnam’s population is unequally distributed in 8 regions with different socio-economic conditions, and hence the dropout situation is also regionally specific. Moreover, the parents’ perception of the value of education may increase the child’s probability of school retention. Since it is difficult to measure parental attitude to schooling, the paper uses parents’ education level instead, assuming that parents who have more education will appreciate education more.
Keywords: Dropping out of school; Probit model; Economics, General (0501)